Influence of Ingestion of Lactulose on γ-Lactones Emanating from Human Skin Surface - Yoshika Sekine; Shiori Uchiyama; Michihito Todaka; Yohei Sakai; Ryo Sakiyama; Hiroshi Ochi; Maho Muramatsu; Satomi Asai; Kazuo Umezawa (Applied Sciences, 2023)
Lactulose is known to grow health-promoting bacteria, with an increase in the production of beneficial metabolites, such as lactic acid and short-chain fatty acids (SCFAs) in the colon. Ingestion of lactulose powder at a food dosage level is known to reduce the dermal emanation of ammonia, a typical human skin gas which potentially affects body odour. However, no study has reported the effect of lactulose on human skin gases other than ammonia. In this study, the influence of lactulose ingestion on the dermal emissions of γ-lactones, volatile cyclic esters with sweet smells, was investigated in healthy subjects. Healthy participants ingested the lactulose powder with a food dosage of 4 g d−1 once a day for 2 weeks. γ-lactones emanating from the skin surface were collected from each participant’s forearm by using a passive flux sampler, and six kinds of γ-lactones, namely, γ-hexalactone (C6), γ-heptalactone (C7), γ-octalactone (C8), γ-nonalactone (C9), γ-decalactone (C10), and γ-undecalactone (C11), were determined by gas chromatography–mass spectrometry. Quantification of bifidobacteria in faeces collected before and after ingestion of lactulose for 2 weeks was carried out by using real-time PCR. The results showed a significant increase in the dermal emission fluxes of sweet-smelling C10 and C11 lactones as the number of bifidobacteria increased in the faeces, presumably mediated by SCFAs produced in the colon.